The Effectivity of Online Learning in Japanese Department Diploma Program in Widyatama University - Amalia, Aan; Ranadireksa, Dinda.G.; Nurohmah, Hety; Aprilani, Felicis; Johari, Abdul Latif (CENTRAL ASIA AND THE CAUCASUS, 2022)
In 2020 the world was attacked by a deadly virus called covid 19, so the United Nations made the condition a pandemic and applied globally. With the pandemic, all life arrangements have changed, including in the field of education, learning is carried out online because people have to keep their distance and cannot gather or gather in large numbers, to prevent transmission of the covid 19 virus. Online learning in the Japanese language study program at Widyatama University was considered effective by students of the Japanese language study program who were respondents in this study. This is because it is supported by a special website that was designed by the IT team and academic team as well as the complete facilities and infrastructure owned by Widyatama University.